1999
DOI: 10.1016/s1097-2765(00)80391-3
|View full text |Cite
|
Sign up to set email alerts
|

C. elegans Dynamin-Related Protein DRP-1 Controls Severing of the Mitochondrial Outer Membrane

Abstract: Little is known about the mechanism of mitochondrial division. We show here that mitochondria are disrupted by mutations in a C. elegans dynamin-related protein (DRP-1). Mutant DRP-1 causes the mitochondrial matrix to retract into large blebs that are both surrounded and connected by tubules of outer membrane. This indicates that scission of the mitochondrial outer membrane is inhibited, while scission of the inner membrane still occurs. Overexpressed wild-type DRP-1 causes mitochondria to become excessively f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

41
521
2
3

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 601 publications
(570 citation statements)
references
References 46 publications
41
521
2
3
Order By: Relevance
“…Immunogold labeling in yeast revealed Dnm1p clustering at constricted sites on mitochondrial tubules that appear to be dividing [9]. Time-lapse imaging of GFP-tagged Dnm1p in S. cerevisiae [10], DRP-1 in C. elegans [27] and Drp1 in mammalian cells [26] showed that mitochondrial tubules divide at sites where these punctate structures are found. Together, these studies provide compelling evidence that cytoplasmic Dnm1p/DRP-1/Drp1 assembles at discrete sites on the outer mitochondrial membranes of all three species, where it plays a direct role in mitochondrial fission.…”
Section: Fission and The Outer Membrane Gtpase Dnm1pmentioning
confidence: 99%
See 2 more Smart Citations
“…Immunogold labeling in yeast revealed Dnm1p clustering at constricted sites on mitochondrial tubules that appear to be dividing [9]. Time-lapse imaging of GFP-tagged Dnm1p in S. cerevisiae [10], DRP-1 in C. elegans [27] and Drp1 in mammalian cells [26] showed that mitochondrial tubules divide at sites where these punctate structures are found. Together, these studies provide compelling evidence that cytoplasmic Dnm1p/DRP-1/Drp1 assembles at discrete sites on the outer mitochondrial membranes of all three species, where it plays a direct role in mitochondrial fission.…”
Section: Fission and The Outer Membrane Gtpase Dnm1pmentioning
confidence: 99%
“…Mutations in several Dnm1p homologs including mammalian Drp1 [26] and Caenorhabditis elegans DRP-1 [27] were also shown to block mitochondrial fission. Conversely, overproduction of Dnm1p [28] and C. elegans DRP-1 [27] increases the number of mitochondrial fragments, suggesting that the rate of fission is limited by the steady-state level of this GTPase.…”
Section: Fission and The Outer Membrane Gtpase Dnm1pmentioning
confidence: 99%
See 1 more Smart Citation
“…Une fois recrutée à la membrane externe, Dnm1/DRP1 oligomérise et forme une spirale dont le changement de structure, induit par l'hydrolyse du GTP, provoque la fission des mitochondries ( Figure 3B). La possibilité de découpler la fission des deux membranes mitochondriales chez C. elegans [11] suggère l'existence d'une machinerie indépendante pour la fission de la membrane interne. Cependant, l'existence d'une telle machinerie n'a pas encore été réellement démontrée.…”
Section: Les Acteurs Et La Mécanistiqueunclassified
“…It has recently been shown that EGL-1 also induces mitochondrial fragmentation, a phenomenon that is observed in apoptotic cells in many species, including the fruitfly Drosophila melanogaster and humans (Herzig and Martinou, 2008;Suen et al, 2008). EGL-1-induced mitochondrial fragmentation depends on the function of the ced-9 gene and is mediated by the dynamin-related GTPase, DRP-1, which is required for mitochondrial fission (Labrousse et al, 1999;Jagasia et al, 2005). DRP-1 has pro-apoptotic activity and can cause CED-4-and CED-3-dependent apoptosis when overexpressed.…”
mentioning
confidence: 99%